2013
DOI: 10.1525/auk.2013.12226
|View full text |Cite
|
Sign up to set email alerts
|

New discoveries in landbird migration using geolocators, and a flight plan for the future

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
135
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(151 citation statements)
references
References 83 publications
(123 reference statements)
11
135
2
1
Order By: Relevance
“…Although staging activity is typically attributed to shorebirds and waterfowl (Dunne et al 1982, Newton 2008, numerous geolocator studies have recently reported passerines making stops ranging from 8 to 36 days (Heckscher et al 2011,Åkesson et al 2012, Delmore et al 2012, Tøttrup et al 2012, Callo et al 2013, Fraser et al 2013, Jahn et al 2013, Kristensen et al 2013, Renfrew et al 2013, Wolfe and Johnson 2015, Van Loon et al 2017 that are analogous in length to staging events. Stops of .7 days surpass the amount of time theoretically expected for migratory refueling under optimality models (Alerstam 1991) and have been classified as ''prolonged stopover''-a behavior distinct from typical songbird stopover (McKinnon et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although staging activity is typically attributed to shorebirds and waterfowl (Dunne et al 1982, Newton 2008, numerous geolocator studies have recently reported passerines making stops ranging from 8 to 36 days (Heckscher et al 2011,Åkesson et al 2012, Delmore et al 2012, Tøttrup et al 2012, Callo et al 2013, Fraser et al 2013, Jahn et al 2013, Kristensen et al 2013, Renfrew et al 2013, Wolfe and Johnson 2015, Van Loon et al 2017 that are analogous in length to staging events. Stops of .7 days surpass the amount of time theoretically expected for migratory refueling under optimality models (Alerstam 1991) and have been classified as ''prolonged stopover''-a behavior distinct from typical songbird stopover (McKinnon et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Stops of .7 days surpass the amount of time theoretically expected for migratory refueling under optimality models (Alerstam 1991) and have been classified as ''prolonged stopover''-a behavior distinct from typical songbird stopover (McKinnon et al 2013). Although it is still unclear why songbirds exhibit this behavior, these extended stops may be an adaptive strategy for accumulating large fat stores at food-rich sites to fuel long migratory flights (Tøttrup et al 2012, Callo et al 2013), especially just before or after a barrier (Delmore et al 2012, Fraser et al 2013, Gómez et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations